BIOLOGICAL GAS RECEIVING AND APPLICATION (American Journal of Pedagogical and Educational Research, 2023)
The shortage of energy resources in the whole world and the constant increase in their price are directing world scientists to search for new ways of using renewable energy sources. Another direction in which the process of energy production from renewable sources is rapidly developing all over the world is the problem of environmental protection. The ecological problem calls for increasing the positive attitude towards nature day by day.